(untitled) (The International Journal of Educational Sciences and Arts, 2026)
Social media platforms serve as virtual communities where communication, interactions, and social connections arise, significantly influencing the formation of individuals’ cultural identities. Humor is one of the cultural elements that spreads widely across the virtual world, which originated through social media, and the youth category is one of the strong groups that follow digital content, and young people are usually attracted to humorous content in particular, which reflects their daily experiences. Through young people sharing jokes and humor, the bonds between them are strengthened and their sense of collective identity is enhanced. Humor circulating on social media also influences the behavior of young people, serving as a tool for expressing opinions and alleviating daily and life pressures. Despite the positive aspects observed in the dissemination of humorous content across various social segments in general، and among young people in particular, we cannot ignore the negative effects some of it can have Humor can manifest in social interactions as mockery and bullying, highlighting the dangers of the rapidly spreading humor found in the digital sphere. Therefore, this research aims to examine the role and risks of humor disseminated through social media platforms, which significantly influences young people’s opinions on social issues. Humor is a powerful and accessible tool for attracting attention, as it simplifies concepts and presents issues in a straightforward and humorous way that captures interest and sparks discussions on all topics relevant to society. The social survey method was used to analyze and study the phenomenon, employing a questionnaire as the data collection tool for the research topic. The study was conducted on a purposive, random sample of 50 individuals, distributing the questionnaire to students at the University of Mosul. The research yielded several key findings, including: - Social media platforms are important for disseminating and acquiring knowledge, communicating with others, and opening channels for social interaction and the exchange of experiences. - Humor circulating on social media provides a platform for young people to freely express their desires and opinions on local and global social issues. - The humor promoted and shared by young people is a double-edged sword, depending on the topics discussed, the methods of presentation, and the individuals and situations depicted.